2017
DOI: 10.1037/xge0000310
|View full text |Cite
|
Sign up to set email alerts
|

Seeing “what” through “why”: Evidence from probing the causal structure of hierarchical motion.

Abstract: Although our world is hierarchically organized, the perception, attention, and memory of hierarchical structures remain largely unknown. The current study shows how a hierarchical motion representation enhances the inference of an object's position in a dynamic display. The motion hierarchy is formed as an acyclic tree in which each node represents a distinctive motion component. Each individual object is instantiated as a node in the tree. In a position inference task, participants were asked to infer the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Previous research has shown that causal inference and the perception of co-occurrence in events are strongly related. Causal inference can affect the perceptual organization of events: Since Heider (1958), psychologists have seen causal inference as a means of imposing order on the environment, and organizing multiple stimuli into coherent units or Gestalts (Read, Vanman, & Miller, 1997;Xu, Tang, Zhou, Shen, & Gao, 2017). Conversely, causal inference is strongly influenced by the perception of at least two kinds of regularity.…”
Section: Lessons From the Literature On Co-occurrence And Causal Infementioning
confidence: 99%
“…Previous research has shown that causal inference and the perception of co-occurrence in events are strongly related. Causal inference can affect the perceptual organization of events: Since Heider (1958), psychologists have seen causal inference as a means of imposing order on the environment, and organizing multiple stimuli into coherent units or Gestalts (Read, Vanman, & Miller, 1997;Xu, Tang, Zhou, Shen, & Gao, 2017). Conversely, causal inference is strongly influenced by the perception of at least two kinds of regularity.…”
Section: Lessons From the Literature On Co-occurrence And Causal Infementioning
confidence: 99%
“…Understanding motion perception as Bayesian inference has a rich scientific history [10,11,16,[23][24][25][26][27]. Bayesian models of low-level perception [23][24][25] were extended to explain human multiple object tracking of independent dot movement [16,27].…”
Section: Discussionmentioning
confidence: 99%
“…Our work extends this line of research to structured motion, revealing the use of structured motion priors during tracking. Our aim to resolve the fine structure of human motion priors led to the development of a novel probabilistic multiple object prediction task that augments single object prediction [11] with velocity covariances within a tractable protocol. Including posterior covariance matrices in the observer model greatly enhanced the log-likelihood ratios in the prediction task beyond the resolution achievable in single object prediction (see Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations